EFFECTIVENESS OF USING INNOVATIVE TECHNOLOGIES IN TEACHING MATHEMATICS IN PRIMARY GRADES - Boboyeva Muyassar Norboyevna (Лучшие интеллектуальные исследования, 2024)
Abstract. This article talks about the effectiveness of using innovative technologies in the process of teaching mathematics in elementary grades. Examples of innovative technologies that can be used in the course of the lesson are presented. The issue of using didactic games in the process of teaching mathematics in elementary grades was analyzed. It is noted that the level of organization of lessons depends on the teacher's creativity. It is noted that didactic games provide an opportunity to individualize the work in the lesson, assign tasks to the strengths of each student, and develop his abilities to the maximum. It is said that through the game, students will consolidate the knowledge they have learned from the lesson and prepare to apply it to life.